Induction of labor with an unfavorable cervix: how does BMI affect success?‡. (16th September 2016) - Lassiter, Jacob R.; Holliday, Nicolette; Lewis, David F.; Mulekar, Madhuri; Abshire, Jacob; Brocato, Brian
Abstract: Objective : Obesity places women and their babies at risk for obstetric and perinatal morbidity including induction of labor and cesarean delivery. We sought to evaluate the impact of body mass index (BMI) on successful induction of labor using misoprostol at our institution. The primary outcome was time to delivery. Secondary outcomes were number of doses of misoprostol, duration of oxytocin and cesarean delivery. Methods : A retrospective cohort over two years found 329 patients who were  > 37 weeks of gestational age and had a Bishop score  < 5 prior to beginning induction. Patients were divided into three categories based on their BMI: Group 1: BMI ≤ 30 kg/m 2, Group 2: BMI 30 to 39.9 kg/m 2 and Group 3: BMI ≥ 40 kg/m 2 . Statistical analysis included the use of multivariate analysis, contingency tables and Chi-square tests for categorical data and Pearson's correlation coefficient for numerical data. Results : There were no significant differences among the groups when analyzed for gestational age, bishop score, median parity or race. Time to delivery increased significantly with increasing BMI ( p  < 0.01). Furthermore, women with higher BMIs required more doses of misoprostol ( p  < 0.01), longer duration of oxytocin administration prior to delivery ( p  < 0.02) and increased risk of cesarean section ( p  < 0.0006). Conclusion : As BMI increases, obese patients undergoing induction with misoprostol have a longer time to delivery, require more doses of misoprostol, require a longer duration of oxytocin and have higher cesarean delivery rate.